Experimental investigation of Mechanical properties in friction welding parameters for dis-similar metals (SS-304 & SS-410). (2021) - Vivekananthan, M.; Saravanakumar, M.; Nimel Sworna Ross, K.; Solai Senthil Kumar, K.; Steephun Raj, F.
Abstract: This paper mainly concentrated on the joining the different grades of stainless steel by the friction weld process. Stainless steel 304 and Stainless steel 410 are the class of iron based materials which has positive resistance to rusting and to corrosion in specific environments. Due to its good properties, it is the commonly used material in the engineering applications. Maximum of stainless steel welding's are prepared by fusion welding. The effect of process parameter speed, friction time and forging time were studied. More over the joint strength is measured by the tensile test and Hardness of the joints.